Gene Therapy to the Retina and the Cochlea - Crane, Ryan; Conley, Shannon M.; Al-Ubaidi, Muayyad R.; Naash, Muna I. (Frontiers in Neuroscience, 2021)
Vision and hearing disorders comprise the most common sensory disorders found in people. Many forms of vision and hearing loss are inherited and current treatments only provide patients with temporary or partial relief. As a result, developing genetic therapies for any of the several hundred known causative genes underlying inherited retinal and cochlear disorders has been of great interest. Recent exciting advances in gene therapy have shown promise for the clinical treatment of inherited retinal diseases, and while clinical gene therapies for cochlear disease are not yet available, research in the last several years has resulted in significant advancement in preclinical development for gene delivery to the cochlea. Furthermore, the development of somatic targeted genome editing using CRISPR/Cas9 has brought new possibilities for the treatment of dominant or gain-of-function disease. Here we discuss the current state of gene therapy for inherited diseases of the retina and cochlea with an eye towards areas that still need additional development.